Traumatic posterior glenohumeral dislocation: A case report - Silva-Ocas, Isabel (2020)
Introduction. The posterior glenohumeral dislocation (PGD) is misdiagnosed frequently. This is associated with high-energy trauma, sports, seizures and electrocutions. The diagnosis is often omitted because of in most of the cases a striking deformity is not seen in the injured joint. Also, initial x-ray images are very similar to those from an uninjured shoulder. A 30-year-old man was admitted to the emergency room after falling onto his left shoulder, no joint deformity was observed. Anteroposterior and transthoracic X-ray showed PGD. Closed reduction was performed under general anesthesia. At 4-year follow-up, the patient has no sequels and preserves joint mobility without pain.